Characteristics of non‐culprit plaques in acute coronary syndrome patients with calcified plaque at the culprit lesion. Issue 3 (28th May 2020) - Kim, Hyung Oh; Kim, Chong Jin; Cho, Jin‐Man; Soeda, Tsunenari; Kurihara, Osamu; Russo, Michele; Araki, Makoto; Lee, Hang; Minami, Yoshiyasu; Jang, Ik‐Kyung
Abstract: Objectives: To investigate the non‐culprit plaques (NCPs) characteristics in acute coronary syndrome (ACS) patients with calcified plaques (CP). Background: Recently, a new in vivo classification of calcified culprit plaques in patients with ACS was proposed. Characteristics of NCPs in this group of patients are unknown. Methods: A total of 692 NCPs from 492 ACS patients were retrospectively compared based on the culprit plaque phenotype: 71 from CP patients, 383 from plaque rupture (PR) patients, 238 from plaque erosion (PE) patients. Results: NCPs of CP patients had greater maximal calcium thickness, wider calcium arc, longer calcium length, and greater calcium index, compared to PR or PE patients (CP vs. PR: all p  < .001, CP vs. PE: all p  < .001). Thin‐cap fibroatheroma was less prevalent ( p = .023), fibrous cap was thicker ( p = .035), and mean lipid arc was narrower in CP than in PR ( p  < .001). Conclusions: In conclusion, NCPs of CP patients had greater calcium burden and less vulnerability. This information may help to better understand the underlying mechanisms of ACS and to develop strategy for tailored management.